PERAN GURU DALAM INTERAKSI SOSIAL ANAK BERKEBUTUHAN KHUSUS (TUNAGRAHITA) UNTUK MENCAPAI KEBERFUNGSIAN SOSIAL (Studi Di SLB B-F Mandara Kota Kendari) - Nurpaisah Nurpaisah; Sulsalman Moita; Meegawati Asrul Tawulo (WELL-BEING: Journal of Social Welfare, 2023)
This study aims to determine the role of the teacher in helping mentally retarded children achieve their social functioning and the difficulties of children with special needs with mental retardation in achieving their social functioning. This type of research uses evaluative qualitative methods with a descriptive approach. Informant learning in this study used purposive sampling so that the research informants were the principal of SLB B-F Mandara Kendari City, 5 mentally retarded homeroom teachers, 6 mentally retarded students and 4 mentally retarded students’ parents. The types and sources of data used in this research are primary data and secondary data. The data collection technique used is the method of observation, interviews, and documentation. Data analysis techniques using data reduction, data testing and drawing conclusions. The results of the study show that 1) The role of thr teacher in helping mentally retarded children achieve their social functioning includes: demonstrator, communicator, mediator, motivator, evaluator, and educator. 2) Overcoming what is experienced by children with mental retardation including: inability to communicate, lack of role of mentally retarded children in doing group assignments (both for practice or in helping work on group discussion questions, easily environment, learning difficulties this is influenced by low IQ, has a less smelly attitude and tends to be quiet in class and in the surrounding environment, intellectual limitations, and difficulty controlling emotions.